2000
DOI: 10.1291/hypres.23.561
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between T-786.RAR.C Mutation in the 5'-Flanking Region of the Endothelial Nitric Oxide Synthase Gene and Essential Hypertension.

Abstract: Accumulating evidence strongly suggests that an alteration in nitric oxide metabolism is involved in the pathogenesis of hypertension. We recently found 2 polymorphisms in the endothelial nitric oxide synthase (eNOS) gene, a GIu298Asp missense variant in exon 7 and a T-786-'C variant in the 5'-flanking region, which are not linked to each other. In our previous reports, we showed a positive association between the GIu298Asp variant and essential hypertension, myocardial infarction, and coronary spastic angina.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
2
19
0
2
Order By: Relevance
“…Interestingly, a statistical difference in the genotype of rs1800780 locus was first found between the EH patients and control cohorts in the Chinese Hui population, where the genotype of AG was more frequent in the EH patients (P > 0.05, Table 3). However, in agreement with the study in Japanese groups, there was no significant difference in the polymorphisms of the rs2070744 (T>C) (T786C) and rs3918181 (A>G) sites between the EH patients and non-EH controls in this ethnic group (P > 0.05, Table 3) (Kajiyama et al, 2000). The G allele of the rs1799983 (G>T) (G894T) SNP was significantly less common in EH patients than in controls (P < 0.05) [OR = 3.851, 95% confidence interval (95%CI) = 2.236-6.631], while the T allele of this SNP was significantly more common in EH patients than in controls (P < 0.05) (OR = 0.260; 95%CI = 0.151-0.447) ( Table 3).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, a statistical difference in the genotype of rs1800780 locus was first found between the EH patients and control cohorts in the Chinese Hui population, where the genotype of AG was more frequent in the EH patients (P > 0.05, Table 3). However, in agreement with the study in Japanese groups, there was no significant difference in the polymorphisms of the rs2070744 (T>C) (T786C) and rs3918181 (A>G) sites between the EH patients and non-EH controls in this ethnic group (P > 0.05, Table 3) (Kajiyama et al, 2000). The G allele of the rs1799983 (G>T) (G894T) SNP was significantly less common in EH patients than in controls (P < 0.05) [OR = 3.851, 95% confidence interval (95%CI) = 2.236-6.631], while the T allele of this SNP was significantly more common in EH patients than in controls (P < 0.05) (OR = 0.260; 95%CI = 0.151-0.447) ( Table 3).…”
Section: Resultssupporting
confidence: 90%
“…Previous polymorphic studies revealed a positive association of rs1799983 (G>T) (G894T mutation) of the eNOS gene with susceptibility to EH in various ethnic groups (Chen et al, 2001;Zhang et al, 2006;Khawaja et al, 2007;Tang et al, 2008;Li, 2011;Men et al, 2011;Niu and Qi, 2011). In contrast, the rs2070744 (T>C) variant (T786C mutation) was reported to lack an association with EH in Chinese Kazakh and Japanese groups (Kajiyama et al, 2000;Deng et al, 2007). Consistent with these findings in other ethnic populations, such as Chinese Han (Niu et al, 2011;Chen et al, 2012), Hani (Tang et al, 2008), Yi (Tang et al, 2008), and Uygur (Zhang et al, 2006) in China, polymorphism of rs1799983 (G>T) in the eNOS gene was found to be a risk factor of EH, while rs2070744 (T>C) polymorphism lacked an association with EH, in the Chinese Hui ethnic population in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous case-control studies, neither NOS3 variation in intron 4 4,8 -12,29,30 nor T(-786)C substitution 31,32 is associated with blood pressure levels, but the physical activity levels are not taken into consideration in these studies. Similarly, in our study, before the subjects were divided into three physical activity level groups, the prevalence of systolic hypertension was not significantly different between aaϩba and bb groups (ORϭ1.2; 95% CI, 0.8 to 2.0).…”
Section: Discussionmentioning
confidence: 91%
“…BP was measured using a sphygmomanometer while the patient was in a supine position. A group of 170 normotensive control subjects were selected from the same clinics according to the following criteria: 1) subject age > 30 years; 2) systolic/diastolic BP < 140/90; and 3) absence of antihypertensive treatment (16,17). At the time of recruitment, informed consent was obtained from each person according to the protocol approved by the Human Study Committee of Kyoto University.…”
Section: Patient Populationmentioning
confidence: 99%